General anaesthesia versus local anaesthesia for carotid surgery (GALA): a multicentre, randomised controlled trial. - Lewis, S; Warlow, C; Bodenham, A; Colam, B; Rothwell, P; Torgerson, D; Dellagrammaticas, D; Horrocks, M; Liapis, C; Banning, A; Gough, M; Gough, M (2008)
BACKGROUND: The effect of carotid endarterectomy in lowering the risk of stroke ipsilateral to severe atherosclerotic carotid-artery stenosis is offset by complications during or soon after surgery. We compared surgery under general anaesthesia with that under local anaesthesia because prediction and avoidance of perioperative strokes might be easier under local anaesthesia than under general anaesthesia. METHODS: We undertook a parallel group, multicentre, randomised controlled trial of 3526 patients with symptomatic or asymptomatic carotid stenosis from 95 centres in 24 countries. Participants were randomly assigned to surgery under general (n=1753) or local (n=1773) anaesthesia between June, 1999 and October, 2007. The primary outcome was the proportion of patients with stroke (including retinal infarction), myocardial infarction, or death between randomisation and 30 days after surgery. Analysis was by intention to treat. The trial is registered with Current Control Trials number ISRCTN00525237. FINDINGS: A primary outcome occurred in 84 (4.8%) patients assigned to surgery under general anaesthesia and 80 (4.5%) of those assigned to surgery under local anaesthesia; three events per 1000 treated were prevented with local anaesthesia (95% CI -11 to 17; risk ratio [RR] 0.94 [95% CI 0.70 to 1.27]). The two groups did not significantly differ for quality of life, length of hospital stay, or the primary outcome in the prespecified subgroups of age, contralateral carotid occlusion, and baseline surgical risk. INTERPRETATION: We have not shown a definite difference in outcomes between general and local anaesthesia for carotid surgery. The anaesthetist and surgeon, in consultation with the patient, should decide which anaesthetic technique to use on an individual basis. FUNDING: The Health Foundation (UK) and European Society of Vascular Surgery.